2023
DOI: 10.1080/21645515.2023.2176083
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine literacy: A scoping review

Abstract: To address vaccine hesitancy, specific self-rated tools have been developed to assess vaccine literacy (VL) related to COVID-19, including additional variables, such as beliefs, behavior, and willingness to be vaccinated. To explore the recent literature a search was performed selecting articles published between January 2020 and October 2022: 26 papers were identified using these tools in the context of COVID-19. Descriptive analysis showed that the levels of VL observed in the studies were generally in agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 117 publications
2
27
0
Order By: Relevance
“…These results are consistent with those of a study conducted in the United States that found a correlation between vaccine reluctance and factors such as gender, race (particularly African-American and American Indian/Alaska Native), smoking, socioeconomic status, regular use of social media, food insecurity, and lack of access to healthcare (40). Researchers found that people's knowledge of the COVID-19 vaccine was linked to their vaccination history, age, level of education, and even, maybe, gender (41). According to another American study, HL serves as a source of wealth when dealing with a pandemic since it allows for the speedy acquisition of accurate knowledge, the comprehension of social hazards, and the adoption of restrictive government laws and protective behaviors (42).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of a study conducted in the United States that found a correlation between vaccine reluctance and factors such as gender, race (particularly African-American and American Indian/Alaska Native), smoking, socioeconomic status, regular use of social media, food insecurity, and lack of access to healthcare (40). Researchers found that people's knowledge of the COVID-19 vaccine was linked to their vaccination history, age, level of education, and even, maybe, gender (41). According to another American study, HL serves as a source of wealth when dealing with a pandemic since it allows for the speedy acquisition of accurate knowledge, the comprehension of social hazards, and the adoption of restrictive government laws and protective behaviors (42).…”
Section: Discussionmentioning
confidence: 99%
“…10,13 This has been further fuelled by opinions on social media, within social networks 69 and poor vaccine literacy among healthcare professionals. 70 However, what is clear is that COVID-19 vaccination in pregnancy is safe. 71 When considering maternal and fetal adverse outcomes, several studies have investigated vaccines in pregnant women.…”
Section: Sa R S -C Ov-2 Vac CI Nat Ionmentioning
confidence: 99%
“…Vaccine safety is a concern for many women, perhaps fuelled by a lack of clear messaging at the start of the pandemic, with pregnant women not included in clinical trials, 12 followed by a relative delay in the national recommendations for vaccination 10,13 . This has been further fuelled by opinions on social media, within social networks 69 and poor vaccine literacy among healthcare professionals 70 . However, what is clear is that COVID‐19 vaccination in pregnancy is safe 71 …”
Section: Sars‐cov‐2 Vaccinationmentioning
confidence: 99%
“…In terms of stability of results, sensitivity analysis was used for validation to exclude outliers from the study. In the subgroup analysis, the following variables were included: (1) the type of health behavior, divided into two categories: preventive health behavior and health promotion behavior (we considered a strong heterogeneity between the two categories), and in addition, due to the speci city of the COVID-19 vaccination behavior, which both prevents viruses and promotes immunity, and due to its positive meaning of active immunity, it was de ned as HPB (Biasio et al 2023), (2) outcome, (3) country/region, (4) study design, (5) research form, (6) behavioral intention, (7) population, and (8) theoretical basis, with the above eight categorical variables for subgroup analysis as well as four continuous variables for meta-regression analysis so as to analyze moderating effects: (1) cultural tightness, (2) individual collectivism score, (3) gender ratio, and (4) mean age. In the subgroup analysis, studies with k (i.e., effect size) less than 3 will be excluded.…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%